Implementation of the subject 'Operations Management' on the University of Oviedo's virtual education tool 'Virtual Campus'. (20th January 2010) - Parreno, Jose; Puente, Javier; Ordonez De Pablos, Patricia; Priore, Paolo
According to Bologna's Declaration and consequent introduction of the European Space of Higher Education, virtual educational tools implementation is an almost mandatory task for every University around Europe. Since 1999, Spain's University of Oviedo has been developing a virtual education tool called 'Virtual Campus' to help professors to undertake a new and more modern way of teaching and interacting with students. Implanting a subject in University of Oviedo's 'Virtual Campus' entails a continuous monitoring by the professor of the students performance, as well as adding educational materials to be used by students. In this paper, the design and implementation of the subject 'Operations Management' in 'Virtual Campus' is addressed. This subject belongs to the fourth year of the Industrial Engineering studies in the University of Oviedo at Gijon. Besides presenting the design and implementation of this subject in 'Virtual Campus', the design, results and conclusions of a survey in which the students had the chance to share their experiences with the use of this virtual educational tool are presented in this work.